2017
DOI: 10.4236/ojapps.2017.712047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Extracellular and Intracellular Magnetic Hyperthermia Treatments Using Magnetic Particle Imaging

Abstract: The purpose of this study was to evaluate the effectiveness of intracellular magnetic hyperthermia treatment (MHT) in comparison with that of extracellular MHT using magnetic particle imaging (MPI). Colon-26 cells were implanted subcutaneously into the backs of 8-week-old male BALB/c mice. When the tumor volume reached approximately 100 mm 3 , the mice were divided into control (n = 10), extracellular MHT (n = 8), and intracellular MHT groups (n = 7). In the control group, MHT was not performed. In the extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…In vitro , magnetic hyperthermia using ScreenMAG particles was remarkably efficient in inducing cell death after 1 h. Moreover, intracellular ScreenMAG are more cytotoxic than extracellular ScreenMAG. This result is in agreement with a previous study 39 . Since the temperature elevation ranged between 43 and 50 °C for intracellular ScreenMAG, the cell death is probably apoptosis as described in Cortie et al 40 .…”
Section: Discussionsupporting
confidence: 94%
“…In vitro , magnetic hyperthermia using ScreenMAG particles was remarkably efficient in inducing cell death after 1 h. Moreover, intracellular ScreenMAG are more cytotoxic than extracellular ScreenMAG. This result is in agreement with a previous study 39 . Since the temperature elevation ranged between 43 and 50 °C for intracellular ScreenMAG, the cell death is probably apoptosis as described in Cortie et al 40 .…”
Section: Discussionsupporting
confidence: 94%
“…To understand whether or not this affects the therapeutic outcome further experiments are needed. It is worth mentioning that it was recently shown that cell death induced in vivo on colon tumours after application of MH treatment occurred without a significant global temperature increase 60 .…”
Section: B Specific Absorption Rate Measurementsmentioning
confidence: 99%
“…We note that the theranostic potential of MPI extends far beyond guiding cell-based treatments. Although this review focuses on MPI imaging applications, extensive work has also been performed demonstrating the utility of MPI for ionizing radiation-free surgical guidance 3437 and therapeutic guidance, such as with magnetic hyperthermia 3842 .…”
Section: Cell Trackingmentioning
confidence: 99%